2006
DOI: 10.1207/s15326942dn3003_6
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Subtypes on the California Verbal Learning Test–Children's Version After Pediatric Traumatic Brain Injury

Abstract: The purpose of this study is to determine the presence of profile subtypes on the California Verbal Learning Test-Children's Version (CVLT-C; Delis, Kramer, Kaplan, and Ober, 1994) in 175 children with traumatic brain injury (TBI). Four key z score variables are used in a 2-stage cluster analysis that reveal 4 reliable subtypes. No meaningful differences among the clusters are found on demographic variables. In contrast, statistically significant differences among the 4 clusters in both level and pattern of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…20 Cluster analysis has been used in cross-sectional studies of cognitive function after TBI in childhood. [23][24][25][26] From the abovementioned literature it is clear that a personoriented method of data analysis has the potential to expand our understanding of outcomes after TBI in childhood. In this study of cognitive development and recovery after childhood TBI, we used cluster analysis to investigate acute stage profiles of injury age and four indicators of cognitive function, measured by Wechsler Index scores.…”
Section: Introductionmentioning
confidence: 99%
“…20 Cluster analysis has been used in cross-sectional studies of cognitive function after TBI in childhood. [23][24][25][26] From the abovementioned literature it is clear that a personoriented method of data analysis has the potential to expand our understanding of outcomes after TBI in childhood. In this study of cognitive development and recovery after childhood TBI, we used cluster analysis to investigate acute stage profiles of injury age and four indicators of cognitive function, measured by Wechsler Index scores.…”
Section: Introductionmentioning
confidence: 99%
“…Brain regions affected by TBI are dependent on the mechanisms of injury, including primary and secondary processes (Gennarelli & Graham, 2005;Mottram & Donders, 2006). However, Power and colleagues (Power, Catroppa, Coleman, Ditchfield, & Anderson, 2007) found that the amount of brain damage, rather than the location, predicted attentional deficits following pediatric TBI.…”
mentioning
confidence: 99%
“…Ward's method of cluster analysis was selected because it is consistent with the cluster analytic methodology of previous studies of neuropsychological variables in children with TBI Curtiss, Vanderploeg, Spencer, & Salazar, 2001 ;Mottram & Donders, 2006 ;Thaler et al, 2010 ), its results are consistent with those produced by other agglomerative clustering methods, and compared to these other methods, it is less affected by outliers (Morris, Blashfi eld, & Satz, 1981 ). The squared Euclidian distance coeffi cient was selected because it provides a direct measure of distance between objects in Euclidean space and is sensitive to both pattern and level of performance differences (Everitt, Landau, & Leese, 2001 ).…”
Section: Discussionmentioning
confidence: 99%